Structure, mineralogy and geochemistry of the Amesmessa gold ore deposit in the Algerian Sahara - E. . Aouli; S. V. Belov (Известия высших учебных заведений: Геология и разведка, 2015)
The geological structure, mineralogical and geochemical features of the Amesmessa gold quartz-vein type ore deposit located in In-Uzzal region of Hoggar shield (the Algerian Sahara) are described. The ore-bearing object has Proterozoic age and belongs to the gold - quartz - low-sulfide formation. The basis of its structure and a typical geological setting of the ore veins location are the fault paragenesis that had arisen in a process of the development of a big fault zone during the Ebourneisky tectonic and magmatic cycle. This object belongs to a formation typical for the metallogenic zones of the green belts of the ancient shields and has good prospects of accumulation of the ore resource potential.